2020
DOI: 10.1039/d0ta01664k
|View full text |Cite
|
Sign up to set email alerts
|

A MoO3/MoO2-CP self-supporting heterostructure for modification of lithium–sulfur batteries

Abstract: A unique MoO3/MoO2 heterostructure with an active interface is an ideal host for Li2S8, exhibiting superior rate and long-term cycling performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 48 publications
0
36
1
Order By: Relevance
“…It is reported that combining another compound with MoS 2 to form heterostructures is an efficient way to restrict the shuttle of polysulfides. , Mo-based oxides (MoO x ) are good polysulfides hosts owing to the strong polarity of the metal–oxygen bond . Therefore, MoS 2 –MoO x heterostructures can improve the adsorption ability effectively.…”
mentioning
confidence: 99%
“…It is reported that combining another compound with MoS 2 to form heterostructures is an efficient way to restrict the shuttle of polysulfides. , Mo-based oxides (MoO x ) are good polysulfides hosts owing to the strong polarity of the metal–oxygen bond . Therefore, MoS 2 –MoO x heterostructures can improve the adsorption ability effectively.…”
mentioning
confidence: 99%
“…And as can be observed in follow s‐MoO 3 /MoO 2 @C XRD pattern of Figure 1(f), orthorhombic MoO 3 (PDF#05‐0508), monoclinic MoO 2 (PDF#32‐0671) and some characteristic peaks of transition state molybdenum oxides appear simultaneously, which is considered as MoO 3 and MoO 2 composite materials. The weak diffraction peak indicates that the crystallinity decreases after heat treatment, [19] corresponding to the low crystallinity region in HRTEM.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the MoO 3 /MoO 2 heterostructure delivers an initial specic capacity of 580.5 mA h g À1 at 2.5C with a capacity retention of 82.8% aer 850 cycles. 66 Xu and co-workers combined NiO and NiCo 2 O 4 to produce NiO-NiCo 2 O 4 heterostructure as a sulfur host for Li-S batteries. They found that NiO-NiCo 2 O 4 heterostructure could signicantly promote polysulde conversion reactions and improve the electrical conductivity during cycling.…”
Section: Heterostructuresmentioning
confidence: 99%